2008
DOI: 10.1158/1535-7163.mct-08-0010
|View full text |Cite
|
Sign up to set email alerts
|

Human α-defensin-1 inhibits growth of human lung adenocarcinoma xenograft in nude mice

Abstract: Human A-defensin-1 (HNP1), a small antimicrobial peptide, shows cytotoxicity to tumor cells in vitro and inhibitory activity for pathologic neovascularization in vivo. Here, we did a gene therapy with a plasmid that expresses a secretable form of HNP1 for assaying its antitumor activity. The expression and secretion of HNP1 were determined by reverse transcription-PCR and ELISA in vitro. We found that expression of HNP1 in A549 tumor cells caused significant growth inhibition. This effect is most likely cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 33 publications
(37 reference statements)
2
44
0
2
Order By: Relevance
“…ABC transporters confer a drug-resistant phenotype by decreasing intracellular accumulation of chemotherapeutic drugs via ATP-dependent efflux mechanisms (40). Previously, we found that HNP1 increased plasma membrane permeability in A549 cells (17). In the present research, the intracellular expression of HNP1 caused enhancement of Dox accumulation in 4T1 cells and exhibited a synergistic apoptosis-inducing effect in combination therapy.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…ABC transporters confer a drug-resistant phenotype by decreasing intracellular accumulation of chemotherapeutic drugs via ATP-dependent efflux mechanisms (40). Previously, we found that HNP1 increased plasma membrane permeability in A549 cells (17). In the present research, the intracellular expression of HNP1 caused enhancement of Dox accumulation in 4T1 cells and exhibited a synergistic apoptosis-inducing effect in combination therapy.…”
Section: Discussionsupporting
confidence: 57%
“…Previously, we observed that intracellularly expressed HNP1 increased plasma membrane permeability in human A549 lung carcinoma cells (17). We also noted that the intratumoral expression of HNP1 mediated specific angiogenesis inhibition in vivo (17,18).…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Furthermore, upregulation of HNP1-3 in tumor tissue and plasma has been thought to be a potential marker for prognostic assessment (14,15). We recently also reported that intratumoral expression of HNP1 within human A549 lung carcinoma xenografts resulted in increased cell apoptosis and inhibition of angiogenesis in nude mice (16).…”
mentioning
confidence: 93%